1978
DOI: 10.1104/pp.62.4.636
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Magnetic Resonance Relaxation Times and Plasmalemma Water Exchange in Ivy Bark

Abstract: Measurement of nuclear magnetic resonance (NMR) relaxation times (transverse lT21 and longitudinal IT1I) for Hedera helix L. cv. Thorndale (ivy) bark water hndcates the presence of at least two populations of water with different relaxation characteristics. One population of water with short T2 and T1 was found to be composed of both hydration water and extracellular free water. The second population of water with long T2 and T1 was identified as intracellular bulk water.NMR relaxation of extracellular water p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
1

Year Published

1979
1979
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 19 publications
0
24
1
Order By: Relevance
“…A good fit to the data could be made by assuming that the signal arose from two populations of water, each with a different magnetic environment producing two different relaxation times. Both Burke et al (2) and Stout et al (27) found, as in this study, that at least two populations of water with different relaxation times exist in plant tissue. These two populations of water do not rapidly exchange with each other as evidenced by the difference in relaxation rates.…”
Section: Pulsed Nmr Of Wheat and Rye Crownsmentioning
confidence: 64%
“…A good fit to the data could be made by assuming that the signal arose from two populations of water, each with a different magnetic environment producing two different relaxation times. Both Burke et al (2) and Stout et al (27) found, as in this study, that at least two populations of water with different relaxation times exist in plant tissue. These two populations of water do not rapidly exchange with each other as evidenced by the difference in relaxation rates.…”
Section: Pulsed Nmr Of Wheat and Rye Crownsmentioning
confidence: 64%
“…In ivy bark tissues (Stout et al, 1978) and in wilting leaves (Colire et al, 1988), extracellular and intracellular water have been associated with long and short T 2 , respectively. Water bound in chloroplasts and vacuoles of plant cells shows even longer T 2 values (Snaar and Van As, 1992;Sainis and Srinivasan, 1993).…”
mentioning
confidence: 99%
“…Stout et al [l I] measured water proton relaxation rates in Chloreiia cells suspended in media containing Mn'+; they found a mean residence time of 25 ms for water molecules inside the cells and a diffuSiOnal Water permeability Coefficient (Pd) Of 2.1 x 10m3 cm/s for the cell walls. Pd values for other plant membranes [5,8,9,12] are in the range from about 1 x 10m4 to 5 x lo-' cm/s. Water exchange through the thylakoid membrane inside chloroplasts is fast; Wydrzynsky et al [13], using isolated, broken chloroplasts, measured exchange lifetimes of less than 20 ms.…”
Section: Introductionmentioning
confidence: 97%
“…Water is generally present in plant tissue in two or more compartments that are isolated (on an NMR time scale) by slow exchange rates. The compartments in bark and stems have been identified [7,8] as extracellular and intracellular water. Different relaxation times from vacuolar and cytoplasmic water can be distinguished in maize roots [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation